Wildlife value orientations: construct validity and a qualitative approach to measuring determinants - DeRuiter, Darla S., author; Donnelly, Maureen, advisor; Canetto, Silvia, committee member; Williams, Daniel R., committee member; Vaske, Jerry, committee member (Colorado State University. Libraries, 2002)
This dissertation reports the results from two related studies, one quantitative in nature and one qualitative. Both studies revolve around the values people hold toward wildlife. Chapter I introduces the concepts surrounding wildlife values, provides a literature review, theoretical and methodological background, and organizational information. The first study, found in Chapter II, examines the construct validity of the wildlife value orientation scale. The predictive ability of a new, single-item measure was compared to the existing approach to measuring wildlife value orientations. A survey was administered which included both measures. After reliability of the scale was established, correlations, cluster analysis, and structural equation path models were conducted. Results show that the reliability of the existing scale is consistent with previous studies. The two measures were significantly correlated and had similar structure; however, the multi-item scale was more predictive of attitudes toward local wildlife issues than the single-item measure. While the new measure may prove to be sufficient to replace the existing scales, further research is required, as well as refining that measure. Validity of the wildlife value orientation construct can be tentatively confirmed. The second study (Chapter III), takes an exploratory approach to understanding the determinants of value orientations toward wildlife. Four major dimensions (socialization, experience, personal characteristics, and place) were explored through in-depth interviews with 18 participants. Results suggest that these dimensions are an appropriate way to organize the determinants of wildlife value orientations, but that the combination and importance of the various dimension components fluctuated markedly for different people in the study. Family members, particularly fathers, were important influences common to nearly all respondents. Place of upbringing (rural or urban) played a key role in shaping wildlife value orientations, as did cohort. For some, direct experiences with wildlife were critical. Religiosity and gender were very important to a few participants, but articulation of these influences may be difficult because they are so imbedded in a person's psyche. The manuscript concludes with Chapter IV, which discusses the theoretical, psychometric, and applied implications of the studies. By synthesizing the results from both chapters, a program of future research is presented.
Keywords: recreation; wildlife; values; studies; deer; habitats; attitudes; wildlife conservation; animal populations